In Vitro Bioactivity of Binary Nepheline-Fluorapatite Glass/Polymethyl-Methacrylate Composite - Dalia Y. Zaki; Esmat M. A. Hamzawy (Advances in Materials Science and Engineering)
In vitro bioactivity of stoichiometric nepheline-fluorapatite glass/polymethyl-methacrylate (PMMA (C5O2H8)n) composite was evaluated. Four glasses of nepheline/fluorapatite with different ratios (75/25, 80/20, 85/15, and 90/10 mole%) were added in 20 and 40  wt.% to PMMA. The composite samples were soaked in simulated body fluid (SBF) for 25 days. A scanning electron microscope with energy dispersive X-ray microanalysis (SEM/EDX) and thin film X-ray diffraction analysis was used to evaluate the composite materials after immersion in SBF. Inductively coupled plasma (ICP) and pH changes were used in the determination of the ions released and the alkalinity, respectively, after the immersion in Tris-buffered solution. Effect of glass filler loading on compressive strength of the cements was also evaluated. The four binary nepheline-fluorapatite glasses/PMMA cements composites are good potential bioactive materials. The compressive strength was between 70.36 ± 6.47 and 97.30 ± 3.90 MPa. In general, decreases of the compressive strength follow the increase of the glass ratio (i.e., 40 wt.%), but all meet that specified by the ASTM F-451.